Design and development of fiber bragg grating sensor for detecting of hydrogen gas in transformer oil / Mohd Raffi Samsudin - Mohd Raffi , Samsudin (2020)
Hermetically sealed oil-immersed transformers are the key to electricity distribution networks. They are also one of the most expensive facilities in the electricity supply network. Immediate replacement is expected for this type of transformer upon failure because it is directly connected to the customer. Transformer oil acts as insulation, coolant and condition indicator. To date, there is no economical real-time monitoring system available to monitor the transformer oil condition. Therefore, there is a need to develop a cheap, non-intrusive and non-electrical sensor to monitor the health of the transformer by measuring the amount of dissolved hydrogen gas in oil, which is an early indicator for electrical fault in the transformer. In this research, sixteen fiber Bragg gratings (FBG) sensors which are based on different palladium (Pd) coatings ratios and thicknesses were developed to detect dissolved hydrogen gas content in transformer oil. All the coatings were prepared by using physical vapour deposition technique with a combination of RF and DC methods. All samples have palladium-chromium ratios of 100:0 (Pd100), 88:12 (Pd88Cr12), 75:25 (Pd75Cr25) and 67:33 (Pd67Cr33) and for each composition, four (4) samples were prepared with different coating thicknesses which were 970 nm, 1060 nm, 1180 nm and 1300 nm. TiO2 was used as the adhesion layer between FBG and the Pd-Cr coatings. Initially, the adhesion layer on a test fiber was tested inside heated transformer oil for 40 days before the palladium and chromium coating. The TiO2 coating showed excellent adhesion properties to the fiber because it did not show any signs of surface roughness, uneven thickness, peeling off or microcracking after it was immersed in transformer oil. Transformer oil samples with different dissolved hydrogen contents were then prepared by diffusing hydrogen gas into the oil. The samples were tested by using a portable dissolved gas analyser. All the FBG sensors were tested with separate transformer oil with different levels of dissolved hydrogen, and the wavelength shifts were recorded. The measurement of coating thicknesses and compositions were done by scanning electron microscopy (SEM) and energy dispersive x-ray (EDX) method. On the other hand, a high voltage generator and a spark gap were developed to generate partial discharge in the oil for validation purpose. All sensors were tested with hydrogen gas generated by partial discharge activity, and the errors were less than 10%. Pd100 sensor showed average induced strains of 0.1801 pm/ppm (970 nm of coating thickness) whereas Pd67Cr33 sensor showed the lowest strain of 0.0137 pm/ppm (970 nm of coating thickness). This work has demonstrated a potential of using alloy metal like chromium to the palladium metal to enhance dissolved hydrogen detection range. Different ranges of saturation were shown for all FBG sensors due to different palladium-chromium composition. This sensor has the potential to be used inside the hermetically sealed transformer to detect electrical fault at the early stage. The sensor can be made as a standalone module which may be used to produce fault alarm once hydrogen exceeded specific preset value.